Defecation frequency and timing, and stool form in the general population: a prospective study. Issue 6 (June 1992) - Heaton, K W; Radvan, J; Cripps, H; Mountford, R A; Braddon, F E; Hughes, A O
Abstract : Because the range of bowel habits and stool types in the community is unknown we questioned 838 men and 1059 women, comprising 72.2% of a random stratified sample of the East Bristol population. Most of them kept records of three consecutive defecations, including stool form on a validated six point scale ranging from hard, round lumps to mushy. Questionnaire responses agreed moderately well with recorded data. Although the most common bowel habit was once daily this was a minority practice in both sexes; a regular 24 hour cycle was apparent in only 40% of men and 33% of women. Another 7% of men and 4% of women seemed to have a regular twice or thrice daily bowel habit. Thus most people had irregular bowels. A third of women defecated less often than daily and 1% once a week or less. Stools at the constipated end of the scale were passed more often by women than men. In women of child bearing age bowel habit and the spectrum of stool types were shifted towards constipation and irregularity compared with older women and three cases of severe slow transit constipation were discovered in young women. Otherwise age had little effect on bowel habit or stool type. Normal stool types, defined as those least likely to evoke symptoms, accounted for only 56% of all stools in women and 61% in men. Most defecations occurred in the early morning and earlier in men than in women. We conclude that conventionally normal bowel function is enjoyed by less than half the population and that, in this aspect of human physiology, younger women are especially disadvantaged.